DEVELOPMENT OF WAQF LAND PRODUCTIVITY FOR THE CONTRUCTION OF HOUSING TO LOW INCOME SOCIETY (MBR) FOR REALIZING GENERAL WELFARE - Syawaludin, Saepi; Roestamy, Martin; Sihotang, Sudiman (DERECHTSSTAAT, 2018)
Endowments in Indonesia have abundant potential. However, the potential of waqf has not been able to contribute to solving the problem of poverty, because the management of waqf assets in Indonesia has not been widely used productively due to the still conservative pattern of public thought. Using the Juridical-Normative method, this study tries to provide a literary explanation of the views of the Fuqhas on how the legal status of the development of the productivity of waqf property? and how is the model that can be used to develop the productivity of the waqf property? According to Al-Kamal bin Al-Hammam, the authors of the books Fathul Qadir and Al-Mirginani, the authors of the book Al-Hidayah, said that they could build buildings that were already known that the building could be useful for the ummah, and many models could be used. delivery (BGS) or build operate transfer (BOT).